Academic achievement helps coordination on mutually advantageous outcomes - Isabelle Brocas; Juan D. Carrillo (Proceedings of the National Academy of Sciences, 2025)
This study examines the relationship between academic achievement and strategic ability to coordinate among middle school students. We designed an experimental framework using repeated asymmetric Battle of the Sexes and Hawk–Dove games, to explore how cognitive and social skills related to academic success influence behavior. A total of 132 students participated, divided into groups of high and low academic achievers based on their performance at school. Our results show that, on average, high achievers coordinate better on equilibrium outcomes with simple but effective strategies and obtain higher payoffs compared to low achievers. However, we notice also substantial heterogeneity within groups. Finally, performance in pairs with one high and one low achiever is intermediate but closer to the level of high achievers, suggesting potential peer learning effects and the educational value of mixed groups to promote guidance and joint improvements. These findings suggest that academic success may reflect broader cognitive abilities–such as strategic thinking, anticipation of others’ choices, and cooperation–crucial for navigating real-world interactions in complex environments.